2009
DOI: 10.1590/s0103-21002009000600011
|View full text |Cite
|
Sign up to set email alerts
|

Crianças e adolescentes com história familiar de hipertensão arterial: indicadores de risco cardiovasculares

Abstract: Objective: To identify the risk factor for cardiovascular diseases among children and adolescents with family history of high blood pressure. Methods: Descriptive Study with 141 individuals aged 6 to 18 years from a community in Fortaleza, Brazil. Data were collected at the participants' home. Results: The most common risk factors were salt intake, sedentary lifestyle, and inadequate intake of vegetables. The mean blood pressure was higher among male than female. Conclusion: Early identification of risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…Other Brazilian studies investigated physical exercise among adolescents and found high levels of sedentariness (8,24) . Although most of the population was active in the above results, a significant percentage of insufficiently active adolescents were found, suggesting that the frequency and intensity of the activities practiced may not attend to what is necessary for positive influence on health.…”
Section: Discussionmentioning
confidence: 98%
“…Other Brazilian studies investigated physical exercise among adolescents and found high levels of sedentariness (8,24) . Although most of the population was active in the above results, a significant percentage of insufficiently active adolescents were found, suggesting that the frequency and intensity of the activities practiced may not attend to what is necessary for positive influence on health.…”
Section: Discussionmentioning
confidence: 98%
“…Apesar da importância da identificação precoce de indicadores de risco para a prevenção de eventos cardiovasculares no futuro, essa abordagem é ainda negligenciada em nosso meio para os jovens, mesmo naqueles que têm familiares acompanhados em programas de tratamento de hipertensão arterial. Aparentemente, a orientação dos familiares portadores de hipertensão arterial e que são acompanhados em unidade de saúde não está interferindo no comportamento adotado pelo restante dos membros da família (CHAVES et al, 2009) No que se refere à alimentação, sabe-se que é muito importante realizar as refeições de forma adequada, porém o contexto alimentar de muitos acadêmicos é caracterizado por uma rotina alimentar desequilibrada, causada talvez pelo ingresso na universidade (PETRIBÚ;CABRAL;ARRUDA, 2009). Frutas e verduras são ricas em vitaminas, minerais e fibras e devem estar presentes diariamente nas refeições, pois contribuem para a proteção à saúde, são benéficos na prevenção e tratamento do excesso de peso e do diabetes mellitus.…”
Section: Discussionunclassified
“…Para Chaves et al (2009), os estilos de vida e hábitos saudáveis contribuem para a manutenção da saúde; dessa forma, o controle de fatores de risco, que estão relacionados ao estilo de vida, podem ajudar na prevenção de doenças cardiovasculares. Orho-Melander (2015) destaca que o histórico familiar de hipertensão é um importante fator de risco, para doenças cardiovasculares e doença cardíaca coronariana, elevando o risco de morte.…”
unclassified